2017
DOI: 10.1590/1678-457x.16616
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of stability of bioactive compounds in fruit smoothies

Abstract: Smoothies are drinks composed of a mixture of vegetables (fruits, vegetables), which can be added or not by milk or yogurt, being a high creamy, healthy beverage and a good source of energy, vitamins, and minerals. Samples of three commercial smoothies: Yellow Fruits (YF), Red Fruits (RF), and Green Vegetables (GV) stored in a glass packaging (260 mL) were characterized for pH, soluble solids (°Brix), water activity (aw), density, rheology and thermal properties, and stored at controlled temperatures of 10 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
4
4
0
1
Order By: Relevance
“…The product with the lowest pH was number 17 at 3.31 and the smoothie with the highest pH was number 20 with a pH of 4.06. The results found were in concordance with other studies that previously reported a pH range between 3 and 4 [ 31 , 34 , 35 , 36 , 37 , 38 ]. This acidic pH is very useful when it comes to ensuring microbiological stability, which together with pasteurization treatments or high-pressure processing prevents the proliferation of pathogenic microorganisms and increases the shelf life of the product [ 37 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The product with the lowest pH was number 17 at 3.31 and the smoothie with the highest pH was number 20 with a pH of 4.06. The results found were in concordance with other studies that previously reported a pH range between 3 and 4 [ 31 , 34 , 35 , 36 , 37 , 38 ]. This acidic pH is very useful when it comes to ensuring microbiological stability, which together with pasteurization treatments or high-pressure processing prevents the proliferation of pathogenic microorganisms and increases the shelf life of the product [ 37 ].…”
Section: Resultssupporting
confidence: 93%
“…The results found were in concordance with other studies that previously reported a pH range between 3 and 4 [ 31 , 34 , 35 , 36 , 37 , 38 ]. This acidic pH is very useful when it comes to ensuring microbiological stability, which together with pasteurization treatments or high-pressure processing prevents the proliferation of pathogenic microorganisms and increases the shelf life of the product [ 37 ]. Ingredients such as apples, oranges, lemons, passion fruit, mangos, kiwifruit, mint and red fruits showed a negative correlation with the pH which means that they are good ingredients to add to the smoothies to help to avoid the microorganisms’ spoilage by reducing the pH.…”
Section: Resultssupporting
confidence: 93%
“…The presence of ascorbic acid and other phenolic compounds are responsible for increased antioxidant activities of the beverage. Fu and coauthors [26] evaluated 62 different fruit types and concluded that the antioxidant capacity of fruits varied and the different combinations enhanced the antioxidant activity of the mixed beverage samples and similar supporting results were obtained by Pereira and coauthors [27], Moura and coauthors [28].…”
Section: Effect On Ascorbic Acid and Antioxidant Activitysupporting
confidence: 70%
“…The rheological analysis was performed on rheometer equipment (Brookfield R/S Plus-SST, EUA), with the spindle sensor (V3 40/20 model), with an upward rotation rate of 0 to 60 s, and downward of 60 to 120 s, accelerating for one minute and decelerating for another minute, collecting 50 measurement points, 25 per minute. The tests were carried out at a constant temperature of 25 °C (Moura et al, 2017). The results of shear stress were obtained for each applied strain rate.…”
Section: Rheologymentioning
confidence: 99%